Sebaea solaris (Gentianaceae), a new species from theWestern cape of South Africa - Kissling, Jonathan (My University, 2019)
Sebaea solaris (Gentianaceae) is here described as a new species from the Overberg region, Western Cape, South Africa. This new species is at first glance very distinct from all others in the genus mainly due to its relative large yellow flowers of c. 2.5 cmdiameterwith oblanceolate to obdeltoid erose corolla lobes. The petal ornamentation with several orange lines indicating the flower centre (versus two lines per petal for a few other Sebaea species) and a conspicuous undulated calyx wing are also unique in the genus. Furthermore, the position of large secondary stigmas above the middle of the style (versus at the base of the style for its morphologically closest relative: S. exacoides) possibly indicates differences in pollination strategies.
Keywords: Africa; Cape floristic region; Taxonomy